2020
DOI: 10.3892/ijo.2020.4998
|View full text |Cite
|
Sign up to set email alerts
|

Immune system‑associated genes increase malignant progression and can be used to predict clinical outcome in patients with hepatocellular carcinoma

Abstract: Hepatocellular carcinoma (HCC) is one of the most malignant types of cancer, and is associated with high recurrence rates and a poor response to chemotherapy. Immune signatures in the microenvironment of HCC have not been well explored systematically. The aim of the present study was to identify prognostic immune signatures and build a nomogram for use in clinical evaluation. Using bioinformatics analysis, RNA-seq data and overall survival (OS) information on 370 HCC cases from TCGA and 232 HCC cases from ICGC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 76 publications
1
20
0
Order By: Relevance
“…Then, the KEGG pathway enrichment analysis of these IRDEGs indicated that the primary pathway of IRDEGs is cytokine-cytokine receptor interaction and MAPK signaling pathway (Fig. 1E), and the results are similar to a previous study (17) . The GO analysis showed that the IRDEGs were primarily associated with signaling receptor activator and ligand activity, immune cells migration, chemotaxis, and cytokines secretion, and the response of immune cells to cytokines (Fig.…”
Section: Screening Of Immune-related Differential Genes (Irdegs)supporting
confidence: 87%
“…Then, the KEGG pathway enrichment analysis of these IRDEGs indicated that the primary pathway of IRDEGs is cytokine-cytokine receptor interaction and MAPK signaling pathway (Fig. 1E), and the results are similar to a previous study (17) . The GO analysis showed that the IRDEGs were primarily associated with signaling receptor activator and ligand activity, immune cells migration, chemotaxis, and cytokines secretion, and the response of immune cells to cytokines (Fig.…”
Section: Screening Of Immune-related Differential Genes (Irdegs)supporting
confidence: 87%
“…Numerous studies have demonstrated that the infiltration of tumor-associated immune cells and immune-related genes is correlated with the development and prognosis of HCC ( Duan et al, 2019 ; Huang et al, 2020 ; Tang et al, 2020 ). Remarkably, targeting on these immune cells and/or genes has been a prospective workable approach in HCC therapy ( Jayant et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…The data of the training set were used to generate the prognostic signature through forward conditional stepwise regression with multivariable Cox analysis using the OS-related AR-lncRNAs (Yang et al, 2018 ). A prognostic multi-lncRNA signature was conducted in which the risk score was calculated as follows: ( Coef i was the estimated regression coefficient derived from multivariate Cox regression analysis using the R/survival package (Huang et al, 2020 ), and x i was the expression value of each selected AR-lncRNA). The median risk score in the training set was used as the cutoff point that divided HCC patients into a high-risk group and a low-risk group.…”
Section: Methodsmentioning
confidence: 99%
“…Log-rank testing method was used to compare the differences of OS outcomes between the high- and low-risk groups via Kaplan–Meier survival analysis (Yang et al, 2018 ). The receiver operating characteristic (ROC) curve analysis in the “survivalROC” package (Heagerty and Zheng, 2005 ; Huang et al, 2017 , 2020 ) was applied to examine the accuracy of the identified AR-lncRNA signature. Area under the curve (AUC) of 3-year OS outcomes based on the time-dependent ROC curves was used to compare the prediction accuracy of our newly identified AR-lncRNA signature with other three recently published signatures.…”
Section: Methodsmentioning
confidence: 99%